Ractions in urban and collective memory and transformation of public space: The harbor example in the kyrenia town - ALTAN BAYRAKTAR, Ümmü (My University, 2015)
Nowadays, under the impact of modernization and capitalism, material, social and individual life change in a major pace and scale. The change and evolution of our living spaces in the same pace and scale have lead the people to question the dynamics between past and present. Thus; making research on the relationship between memory and space has brought up; apart from the other studies, the interest to understand the existence of city centers that ensure the sustainability of city and urbanism as a public space, their change and transformation has increased. As a result of recent steps on the economic ration- ality logic, historic- cultural heritage and historic urban patterns have started to be lost. This change and transformation caused fragments in urban and collective memory and stopped the public spaces being living spaces. ‘Harbor’ located in the city of Kyrenia in Cyprus is covered under the scope of this study with its change throughout historical process, physical and social features from the aspects of fragments within urban and collective memory and space and power in the transformation of public space. The theoretical basis of the study is aimed to be the concept of Public Sphere by Jürgen Habermas and Col- lective Memory by Maurice Halbwachs.
Keywords: Public Sphere; Space; Power; Collective Memory; Transformation